Early and rapid diagnosis of Chlamydia psittaci pneumonia by tNGS in six patients: a case series - Yan, Xinsheng; Fu, Huali; Deng, Wenjun; Zhang, Zhenlu; Wang, Dong (Frontiers in Medicine, 2024)
Background: Psittacosis is a zoonotic infectious disease caused by Chlamydia psittaci (C. psittaci) infection, which can be transmitted by birds, poultry and wild animals. The symptoms and imaging findings of C. psittaci pneumonia are atypical and primarily rely on aetiological diagnosis. The incidence of C. psittaci infection has been significantly underestimated because of the low sensitivity and poor timeliness of traditional diagnostic methods. Therefore, early and accurate diagnosis of psittacosis remains a challenge. Case Presentation: A case series with six pneumonia patients who were admitted to our hospital in the period from January 2023 to June 2023 is presented. These patients exhibited acute onset and symptoms, including fever, cough, poor appetite, dry mouth, dizziness, chills, and chest tightness. Despite comprehensive laboratory and radiological examinations, the cause of the pneumonia remained unidentified. Therefore, a sample of bronchoalveolar lavage fluid (BALF) was tested via target next-generation sequencing (tNGS), which revealed a positive result for C. psittaci. Prompt adjustment of the treatment regimens upon identification of the pathogen led to favourable outcomes in all patients. Conclusion: tNGS is a novel diagnostic technology that enables rapid, accurate and costeffective detection of C. psittaci pneumonia. Early detection of C. psittaci can improve patient outcomes through timely adjustment of therapies.